Female Characters' Resistance to Domestication in the Netflix Film Gadis Kretek Series, Simone de Beauvoir's Feminism Studies - Nur Annisa Miftachul Jannah; Firly Annisa (Jogjakarta Communication Conference (JCC), 2024)
The Gadis Kretek series on Netflix (2023) emerged as a phenomenal show upon its debut in November 2023. This series, an adaptation of Ratih Kumala's novel